The Effectiveness Of The Complete Systematic Land Registration Program In The Issuance Of Land Certificates At ATR/BPN Kantah Sukabumi City - Yusdiana Putri, Ressa; FY Basori, Yana Fajar; Meigawati, Dine (Devotion : Journal of Research and Community Service, 2023)
This study aims to determine the effectiveness of the Complete Systematic Land Registration Program (PTSL) in making land certificates at the ATR / BPN Kantah, Sukabumi City. The data collection technique in this study was interviews. While the data analysis technique uses descriptive method with qualitative analysis. Based on the results of research through interviews, it shows that the implementation of the Complete Systematic Land Registration (PTSL) program in Sukabumi City has been effective, it's just that there are still several obstacles that occur and the lack of socialization activities carried out so that there are still many people who do not know about the existence of the program. The National Land Agency (BPN) needs to increase program socialization activities to the community so that people can take part in the Complete Systematic Land Registration (PTSL) program and know more about Complete Systematic Land Registration (PTSL) so that in the future more people can take advantage of it.